2004
DOI: 10.1002/cncr.20105
|View full text |Cite
|
Sign up to set email alerts
|

The use of complementary and alternative medical providers by insured cancer patients in Washington state

Abstract: BACKGROUND Insurance coverage of complementary and alternative medicine (CAM) is expanding. However, to the authors' knowledge, little is know concerning CAM utilization among cancer patients under the insurance model of financing. In this study, the authors evaluated CAM provider utilization by cancer patients in a state that requires the inclusion of alternative practitioners in private, commercial insurance products. METHODS An analysis was carried out of year 2000 claims data from two large Washington Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 26 publications
(35 reference statements)
2
45
1
Order By: Relevance
“…22,24,28,29,34,36,37,39,40,50,51,54,56,[58][59][60]62 The remaining studies collected data from broader study populations and reported the prevalence of CAM use for subgroups including men with prostate cancer. 23,[25][26][27][30][31][32][33]35,38,[41][42][43][44][45][46][47][48][49]52,53,55,57,61,63 The characteristics of all 42 included studies are summarised in Table 2 …”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…22,24,28,29,34,36,37,39,40,50,51,54,56,[58][59][60]62 The remaining studies collected data from broader study populations and reported the prevalence of CAM use for subgroups including men with prostate cancer. 23,[25][26][27][30][31][32][33]35,38,[41][42][43][44][45][46][47][48][49]52,53,55,57,61,63 The characteristics of all 42 included studies are summarised in Table 2 …”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Because surveys vary in terms of definitions of CAM and of specific types of therapy included in questionnaires, the assessment of overall prevalence is somewhat complicated. Noninvasive therapies like acupuncture, chiropractic, massage, spiritual healing, meditation, and imagery are most common, but use of dietary supplements is rapidly gaining terrain [4][5][6][7][8]. As a result, the economic impact of CAM is enormous.…”
Section: Worldwide Use Of Cammentioning
confidence: 99%
“…Although only a small percentage of overall costs are claimed, insurance coverage of CAM is also further expanding [6].…”
Section: Worldwide Use Of Cammentioning
confidence: 99%
“…For example, Washington State has adopted the Every Category of Provider (ECOP) law. 92 The ECOP law states that every category of licensed provider should be included in private health insurance if their scope of practice encompasses medical conditions that the policy covers. Acupuncturists are licensed providers in Washington State.…”
Section: Acupuncture In the Communitymentioning
confidence: 99%